Strategi Mitigasi Risiko Konflik Sosial dalam Pendidikan Islam di Pesantren - Dean Devara Alfari; Wahyu Hidayat (Studia Manageria, 2023)
This study aims to analyze and develop risk mitigation strategies for social conflict in the context of Islamic education at Al-I'tishoom Islamic Boarding School. Social conflict can affect the educational climate and the welfare of students and teaching staff. Therefore, it is important to identify risk factors for social conflict that exist in Islamic boarding schools and formulate effective strategies to overcome and reduce their negative impacts. This research method involves a case study at Al-I'tishoom Islamic Boarding School, by collecting data through interviews, observation, and analysis of related documents. The results of the study show that several risk factors for social conflict exist in Islamic boarding schools including differences in religious views, cultural differences, and socio-economic differences among students. It is hoped that the results of this research can become a reference for education policy makers and related parties in designing effective strategies for managing and reducing the risk of social conflict in the context of Islamic education at the Al-I'tishoom Islamic Boarding School and similar institutions.